The Value of Serum MDA For the Diagnosis of Intracranial Injury - Kavalci, Cemil; Durukan, Polat; Ilhan, Necip; Guzel, Ahmet; Omurlu, Imran Kurt (Aves Yayincilik, Ibrahim Kara, 2008)
Objectives: Malonyldialdehid (MDA) is one of the most sensitive parameters of the lipid peroxidation. In the present study, it was aimed to investigate the value of serum MDA levels in diagnosing intracranial pathologies in minor head trauma. Patients and Methods: This prospective study was approved in Firat University. Patients were categorized into 2 groups: those without intracranial lesions in head CTs (group 1) and those with intracranial lesions in head CTs (group 2). Serum MIDA levels were determined. Results: Mean serum MIDA levels in group 1 (n=50) and group 2 (n=24) were 31.186 +/- 46.9 pg/ml and 54.873 +/- 127.6 pg/ml, respectively. Statistical analysis showed no significant difference between the two groups in terms of MDA values. Conclusion: It is found that serum MDA has limited value in determining the intracranial injury detected with computed tomography in patients with minor head trauma.
Keywords: Emergency department; head trauma; MDA; intracranial injury